Pemberdayaan Perempuan Melalui Lembaga Keuangan Mikro - aljihad, ali; wibowo, arif (Jurnal Pembangunan Manusia, 2022)
The existence of disparities between the human development index of women and men and the mandate of the RPJMN regarding gender equality needs to be considered. Empowerment of women through microfinance has long been implemented and is indeed the main target for microfinance institutions that run it. With so many studies on women's empowerment, there needs to be an analysis of how the forms of empowerment are carried out by microfinance institutions. This writing uses a literature review method which discusses five microfinance institutions from existing research, then analyzes how the forms of women's empowerment are carried out by these financial institutions and how the impact on women who receive them. This paper produces a finding that the empowerment carried out by microfinance is financial intermediation, social intermediation, and capacity building training. The model of microfinance institutions that provides a complete set is referred to as an integrative approach, the impact of the empowerment carried out by these microfinance institutions include opening up women's access to financial services, increasing income and running businesses, as well as increasing self and social capacity. With the services provided by these microfinance institutions, women become more empowered at least at the economic level, such as an increase in income that is in line with the ability to buy, however empowerment has not yet reached a higher socio-political level. This microfinance institution is a steppingstone for women to be empowered at a higher level.